Problematika Pendidikan Agama Islam Bagi Anak Keluarga Buruh Pabrik (Studi Kasus di Lingkungan Dukuh Daleman RT 02/01 Sayung Demak) Tahun 2014/2015 - KHOTIMAH, Khusnul (2016)
Islamic religious education is a very important element in the education of values and morals. To obtain brilliant results should start from the smallest, namely in the family. The role of parents is very important in creating a pious child and sholehah. But in reality, unconsciously they actually treat children in a way away from the realization of these ideals or even plunge to the opposite condition. Lots of parents are busy earning a living. Their activities were very time-consuming, resulting in very little time left to give Islamic religious education, especially educating children. But not many working parents who still pay attention to the needs of children will explore the science of religion, both in the formal and informal institutions such as entering their children into educational park al-Qur'an (TPA) held in the hamlet mosque. The study examined the problems of Islamic religious education for family child factory workers. The formulation of the problem in this research is how the implementation of Islamic religious education for children of factory workers families, and what the advantages and disadvantages of the implementation. The benefits of this research is to increase public awareness, especially in the elderly factory worker on duty to educate their children about the religion of Islam with a good education. This type of research is a field research (field research). Methods of data collection using observation, interviews, documentation, and data analysis. Descriptive qualitative data analysis is comprised of three grooves activity data reduction, data presentation, and conclusion. This study suggests that the implementation of Islamic religious education for family child factory workers less going well, it is evident the problems often faced by parents is the difficulty of parents in guiding their children to perform the duties of Islam such as prayer, chanting, fasting and be polite to older people. In addition, parents can guide their children not directly because of the busyness of parents who work as factory workers and the ability of parents in the education of Islam is very limited. There are some parents who put their children to landfill held at mosques in the hamlet Daleman RT 02 RW 01 Sayung Demak.